Kontribusi Sosial PMMDN Batch 2 Institut Teknologi Kalimantan: Sosialisasi dan Pelatihan Pemanfaatan Limbah Organik menjadi Eco-Enzyme pada Ibu-ibu Rumah Tangga di Desa Beringin Agung, Samboja, Kutai Kartanegara, Kalimantan Timur: Social Contribution of PMMDN Batch 2 Kalimantan Institute of Technology: Training on the Utilization of Organic Waste into Eco-Enzyme for Housewives in Beringin Agung Village, Samboja, Kutai Kartanegara, East Kalimantan - Aan Susiyani; Erny Silaban; Ananda Naufal Rahmatullah; Stela Juni Mawardani; Ulfah Hasbullah; Barokatun Hasanah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
As human beings, in everyday life, they must produce waste, including the residents of the Beringin Agung Village, Samboja, Kutai Kartanegara, East Borneo. There still needs to be more knowledge or skills related to the processing of organic waste owned by residents, which is usually just thrown away without being reused, so the PMMDN Batch 2 ITK students attend by providing socialization and training in making Eco-enzymes. This activity aims to change the mindset of homemakers in the sub-district to get used to Eco-Friendly living, known as Eco-Lifestyle, by utilizing organic waste for daily living needs. This activity was carried out in Beringin Agung Village, in a literacy house Rulika. In making this Eco-enzyme, ingredients are used as brown sugar and granulated sugar, organic waste, and water. Data was collected using a quantitative approach by filling out questionnaires to measure the success rate of the socialization and training done. From the results of processing the questionnaire data, 100% or all participants, As many as 14 people, wrote that they were interested in making it or applying it at home after attending this activity. This shows the level of success of this activity. The socialization and training succeeded in changing the mindset of the homemakers of the Beringin Agung Village to adopt an Eco-friendly lifestyle, often called the Eco-lifestyle.